Integrated vision of the clinical and educational round at Ecuador university hospitals - Roberto Eduardo Aguirre Fernández; Miguel Angel Serra Valdes; Sixto Isaac Chiliquinga Villacís; Brígida Maritza Agudo Gonzabay; Luis Alonso Arciniega Jacome (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The educational and assistance round in the educational-hospital institutions is complex and it is necessary to overcome different goals in the same activity. Objective: To provide a design from current pedagogical conceptions of educational-medical rounds at Ecuadorian university hospitals. Material and Methods: It carried out review of the related bibliography with the pedagogic processes of education in the work of medical formation. Were used the searchers PubMed, Cochrane Library and Google scholar   to know, select, built, analyze and give a systematic view of the educational and assistance round in Ecuador, proposing structural and methodological bases, starting from the Cuban's experience and the own Ecuadorian academic directives. Development: Educational-medical rounds as educational method of  labor to obtain excellence must be more inclusive not using only the clinical method, but also clinical and epidemiological method shall be included and where integrated management objectives must be joined, using pedagogical constructional methods, holistic health-disease environment  through heuristic participation strategies. Conclusion: The use of a proceeding model on a scientific basis properly structured and based on qualitative educational transformations that interrelate with medical caretaking and management issues where patients are evaluated integrally, provides a systemic approach process to this activity.  Keywords: Medical education, teaching methods, education on the job, Ecuador, medical round, doctor, educational, caretaking.